A Model for Evaluating the Procedural and Effectiveness Dimensions of Public Participation in Protected Areas: The SysMAPP - Giovana Cioffi; Davis Gruber Sansolo; Javier García Sanabria (Environmental Management, 2026)
Abstract Despite broad recognition of the role of public participation in protected area (PA) success, persistent barriers highlight the need for tools to monitor and assess participatory processes and outcomes. This study proposes the System for Monitoring and Assessment of Public Participation (SysMAPP), designed to evaluate public participation in PAs by linking procedural conditions and management outcomes. The study is based on a systematic review of existing monitoring and assessment methods, the design of SysMAPP, and its application to PAs in Brazil and Spain. SysMAPP comprises five hierarchically organized, indicator-based criteria: Planning and Representativeness form the foundation of participation; Transparency and Influence connect information flow, accountability, and decision-making power; and Effectiveness captures management outcomes. Crucially, the model unveils the internal logic of participation by demonstrating how these criteria are causally and hierarchically related, showing that procedural and foundational quality directly condition substantive outcomes. SysMAPP also combines standardized core indicators with context-sensitive variables, enabling comparison across protected areas while preserving local governance specificities. Its application revealed contrasting participatory scenarios: strong stakeholder influence in Brazil, primarily through the incorporation of artisanal fisheries agendas, and weak participation in Spain, characterized by the limited representativeness of key groups such as shellfish gatherers and government-centered decision-making. Ultimately, SysMAPP advances beyond traditional scoring by operating as a diagnostic tool for adaptive governance; its results feed back into the management cycle through prioritized adaptation milestones, converting institutional diagnoses into targeted, context-sensitive interventions.